Livinio Stuyck Vandergoten, un flamenco contra Bonaparte - Vidal Galache, Benicia; Vidal Galache, Florentina (Cuadernos de Historia Moderna, 2011)
Up to the Napoleonic invasion, Livinio Stuyck Vandergoten, Director of the Real Fábrica de Tapices - the Spanish Royal Tapestry Factory-, was a successful businessman. He was highly respected by Madrid society, where he hold public offices. During the Peninsular War, Livinio’s business was ruined and his own life repeatedly threatened because of his political opposition to the dictates of the ’rey Intruso’, Joseph Bonaparte, and because of his guerrilla connections. After six years of cruel and devastating war, the Royal Tapestry Factory and Livinio himself suffered the effects of the ruin of the Spanish Treasury. In order to understand fully the attitude and the path of Livinio Stuyck, this paper presents a brief account of the Spanish Royal Tapestry Factory history and also the circumstances of the appointment of the founder of a series of directors who have been more than two centuries at the forefront of this unique company.